The League of Extraordinary Gentlemen : Volume 1 - Moore, Alan, 1953-; O'Neill, Kevin, (Kevin Matthew) (La Jolla, CA : America's Best Comics, 2003)
It's 1898 and at the behest of M, the mysterious head of the secret Service, Campion Bond is dispatched to procure the services of Miss Mina Murray (nee Harker), adventurer Allan Quartermain, "Science-Pirate" Captain Nemo, Henry Jekyll (and his monstrous alter ego) and Hawley Griffin (a.k.a. the Invisible Man). Together, they must combat an insidious threat that will decide supremacy of the London skies, but their success may unleash a far greater threat. With no shortage of action, Moore and O' Neill sustain a high level of suspense, intrigue, mystery and terrific wit that all contribute to an indispensable read. O'Neill's art, so memorable in Marshal Law, produces a London filled with vivid, magnificent architecture and a malevolent atmosphere ripe with thrills and danger.
Description based on v. 2 (2003).
Originally published in single magazine form as The league of extraordinary gentlemen vol. 2, 1-<6>.
Keywords: Graphic Novel; Comics; Comic books, strips, etc